SCHEDULING STUDY ON THE FACULTY OF MEDICINE COLLEGE BUILDING PROJECT INDONESIAN MUSLIM UNIVERSITY - Wudi Darul Putra (UNDERPASS Journal of Civil Engineering, Applied Sciences, and Technology, 2021)
A construction project is an activity that has a certain period of time, with limited resources to carry out a predetermined task in the form of building/repairing facilities (buildings, roads, bridges, dams). This study aims to [1] Optimal scheduling planning in order to obtain maximum profit by using the "S" curve, CPM Network and Analysis of Variance. [2] Get a Project Scheduling scenario that can produce optimal scheduling, in other words the scheduling method that produces the greatest profit. The results showed that [1] In the Scenario of Monthly Payments without Down Payment on Schedule Variant (SV) for 24 weeks, the Cost Variant (CV) was obtained in the form of negative overdraft (-) 17 weeks, positive overdraft (+) at 7 weeks. The biggest overdraft was Rp. 1,412,025,292.00 in the 23rd week. Assuming Profit + Overhead in Unit Price Analysis is 15%, the contractor's potential profit from RAB is 9.71% before tax. [2] In the 20% Advance Payment Scenario with Progress Payments on Schedule Variant (SV) for 24 weeks, the Cost Variant (CV) is obtained in the form of negative overdraft (-) 19 weeks, positive overdraft (+) in 4 weeks, overdraft ( 0) at 1 week. The biggest overdraft was Rp 2,534,761,037.00 in the 19th week. Assuming Profit + Overhead in Unit Price Analysis is 15%, the contractor's potential profit from RAB is 9.24% before tax. [3] In the scenario of 30% Advance Payment with Progress Payment on Schedule Variant (SV) for 24 weeks, the Cost Variant (CV) is obtained in the form of negative overdraft (-) 12 weeks, positive overdraft (+) in 1 week, overdraft ( 0) at 1 week. The biggest overdraft was Rp. 1,599,188,191.00 in the 19th week. Assuming Profit + Overhead in Unit Price Analysis is 15%, the contractor's potential profit from RAB is 10.2% before tax. [4] From the CPM curve, it was found that this project should be carried out using the Earliest Start Time (EST) Scheduling Method, because by shifting activity items to be postponed for 1 week, almost all activity items become part of critical activities. And [5] Cashflow that generates Optimal Profit, namely Payment Scenario with 30% Advance and Progress Payment, and uses Earliest Start Time Scheduling, with potential profit for contractors of 10.2% assuming Profit + Overhead in Unit Price Analysis is 15 %.